The sources of yellow rust resistance (the causative agent Puccinia striiformis West.) among the breeding and collection material of winter wheat developed in the FSBSI “ARC “Donskoy” - G. V. Volkova; I. P. Matveeva; T. G. Derova; N. V. Shishkin; D. M. Marchenko (Зерновое хозяйство России)
The current paper has presented the results of joint long-term immunological study of winter wheat varieties and lines of the FSBSI “ARC “Donskoy” to the North Caucasian population of the yellow rust pathogen. The study was carried out under artificial in fection in various agro-ecological conditions (FSBSI “ARC “Donskoy” in Zernograd, Rostov Region and FSBSI “All-Russian Research Institute of Biological Protection of Plants” in Krasnodar). Yellow rust (the causative agent Puccinia striiformis f. sp. tritici West.) is a dangerous wheat disease in all regions of the world that cultivate grain, including in the south of Russia. In years with favorable conditions, the wheat yield loss caused by this pathogen can reach 70-100%. One of the most effective methods to protect wheat is the cultivation of pathogen-resistant varieties. To develop them, there is a great necessity in a regular screening of resistance sources among wheat varieties and lines of various breeding. In the conditions of field plots the FSBSI “ARC “Donskoy” (2014-2016) and the FSBSI “All-Russian Research Institute of Biological Protection of Plants” (2017-2019) on artificial infectious backgrounds of P. striiformis there were tested the breeding and collection wheat varieties and variety-samples developed by the researcher of the department of winter wheat breeding and seed production of the FSBSI “ARC “Donskoy”. Over the past 40 years, the Don breeders, attracting various sources and donors of resistance, have developed such wheat varieties with high resistance to major diseases, including yellow rust, as “Donskaya bezostaya”, “Don 85”, “Donshchina”, “Kolos Dona”, “Zernogradka 8”, “Don 93”, “Don 95”, “Donskoy Mayak”, etc. As a result of the studies conducted in various agroclimatic zones, among the studied material, there has been established a high percentage (from 52.0 to 87.3) of varieties and varietyyy-samples resistant to yellow rust. According to longterm data, the winter bread wheat varieties “Volnitsa”, “Izyuminka”, “Krasa Dona”, “Lidiya”, “Nakhodka”, “Shef”, “Yubiley Dona”, “Etud” and the winter durum wheat varieties “Zoloto Don”, “Lakomka”, “Uslada” have shown a great resistance to the disease.